Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/adfm.202300147
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Detrimental Effect of Self‐Doping Near the Anode in Highly Efficient Organic Solar Cells

Abstract: Poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) has been one of the most established hole transport layers (HTL) in organic solar cells (OSCs) for several decades. However, the presence of PSS − ions is known to deteriorate device performance via a number of mechanisms including diffusion to the HTL-active layer interface and unwanted local chemical reactions. In this study, it is shown that PSS − ions can also result in local p-doping in the high efficiency donor:non-fullerene acceptor blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Reproduced with permission. [ 129 ] Copyright 2023, Wiley‐VCH. d) Schematic diagram of adhesion enhancement with SEBS.…”
Section: Research Progress On Strategies To Enhance the Stability Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 129 ] Copyright 2023, Wiley‐VCH. d) Schematic diagram of adhesion enhancement with SEBS.…”
Section: Research Progress On Strategies To Enhance the Stability Of ...mentioning
confidence: 99%
“…introduced the 2PACz layer between the PEDOT:PSS layer and the active layer to improve the stability of the device. [ 129 ] The results showed that 2PACz could chemically interact with PEDOT:PSS to achieve closer contact between the interfaces ( Figure 11c). Also, 2PACz can reduce the photocurrent loss caused by nongeminate recombination by inhibiting the formation of an intermixed p ‐doped PSS − ion‐rich region between BHJ/PEDOT:PSS contact interface.…”
Section: Research Progress On Strategies To Enhance the Stability Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] While the secondary dopants are often introduced for busting the conductivity, therefore the processing additives or aftertreatments have been also explored for optimizing the nanostructure of the PEDOT:PSS thin films. [9][10][11] The thin film nanostructure is often focused for modification because the high solubility of PSS allows for the excess PSS remaining in solution while the PEDOT:PSS material aggregates in clusters, and the excess PSS molecules coated on the top of these clusters form an insulating barriers in a core-shell structure. For this reason, acid and polar solvents have been explored for removing excess PSS through soaking or rinsing processes, which results in increased conductivity and tuned energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Only the conducting polymer PEDOT:PSS and the transition metal oxide (TMO) MoO 3 have been widely used as HTLs for modifying anodes, and the best photovoltaic efficiencies in OSCs are obtained by utilizing the PE-DOT:PSS and MoO 3 HTLs. [12][13][14][15] However, the strong acidity of PEDOT:PSS severely degrades device stabilities. And the preparation of MoO 3 through energy-consuming vacuum evaporation certainly limits its use in the large-scale manufacturing.…”
Section: Introductionmentioning
confidence: 99%